ANALISIS FAKTOR-FAKTOR PENENTU TERHADAP KEPUTUSAN MASYARAKAT BERBISNIS SECARA ONLINE DI KOTA TIMIKA - Jhon Handry Siagian; Rulan L Manduapessy (CV. Adiba Aisha Amira, 2025)
This study aims to find out the Determining Factors on the Decision of the Community to Do Business Online in Timika City. The research method used is the Descriptive Method, which is a research method that describes systematically, factually and accurately the facts and characteristics of a particular population or tries to describe the phenomenon in detail. In this study, the data collection techniques used are Observation, Interview, and Questionnaire. The results of the study show that intrinsic and extrinsic factors show that people in running an online business both have an influence on both income factors and community environmental variables.